Causality between Financial Development and Foreign Direct Investment: Evidence from Tanzania - Raphael, Gwahula (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the causal relationship between Foreign Direct Investment (FDI) and Financial Development during the period 1990-2020 in Tanzania. The study aims to shed light on whether FDI inflows have a significant impact on the financial development of the country and vice versa. The analysis employs time series data including GDP, Inflation rate, Formation (capital and Investment), Trade Openness, Country Population size, and Financial Development, to explore the causal links. Using the Granger causality test, the study finds no evidence of causality between FDI and Financial Development, indicating that FDI inflows do not significantly predict changes in financial development, and vice versa. Similarly, the study does not find significant causality between FDI and other control variables such as GDP, Inflation, Formation, and Country Population size. However, there is a significant bi-directional relationship between FDI and Trade Openness, indicating complementarity between FDI and international trade. The results imply that FDI inflows might not be the sole determinant of financial development or other macroeconomic indicators. Policymakers should not solely rely on FDI as a solution to enhance financial development but should focus on creating a conducive environment for FDI and supporting measures that foster financial development independently. The study recommends that policymakers should prioritize strengthening institutions and regulatory frameworks to attract and retain FDI effectively. They should also promote trade liberalization and enhance the domestic financial system to stimulate both FDI inflows and domestic investment.